2021
DOI: 10.1093/mnras/stab624
|View full text |Cite
|
Sign up to set email alerts
|

Low-velocity impacts into granular material: application to small-body landing

Abstract: With the flourishing number of small body missions that involve surface interactions, understanding the mechanics of spacecraft - surface interactions is crucial for improving our knowledge about the landing phases of space missions, for preparing spacecraft operations, and for interpreting the results of measurements made during the surface interactions. Given their regolith-covered surfaces, the process of landing on a small body can be considered as an impact at low-velocity onto a granular material in redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 55 publications
7
27
0
Order By: Relevance
“…The numerical simulations allow us to study the flow of the regolith directly under the rover wheel in more detail. Recent impact experiments have shown that granular material becomes fluidized more quickly under reduced gravity conditions [8]. Here, we look for the transition from the quasi-static to the inertial flow regime when the rover starts moving to see if fluidization of the material in low-gravity restricts the maneuverability of the rover.…”
Section: Resultsmentioning
confidence: 99%
“…The numerical simulations allow us to study the flow of the regolith directly under the rover wheel in more detail. Recent impact experiments have shown that granular material becomes fluidized more quickly under reduced gravity conditions [8]. Here, we look for the transition from the quasi-static to the inertial flow regime when the rover starts moving to see if fluidization of the material in low-gravity restricts the maneuverability of the rover.…”
Section: Resultsmentioning
confidence: 99%
“…Lauretta & DellaGiustina et al 2019 and references therein). Given that these characteristics are fairly well constrained, the sampling attempt can also act as a useful and rare impact experiment onto particles in a microgravity setting, which is difficult to achieve experimentally on Earth (Brisset et al 2018;Bierhaus et al 2021;Murdoch et al 2021). Based on the spacecraft's reaction, and with the added context of the simulations described here, we may be able to better understand the dynamics of granular material in a microgravity environment.…”
Section: S I M U L At I O N S O F O S I R I S -R E X Tag S a M To U C H I N G D Ow N O N B E N N Umentioning
confidence: 99%
“…Low-speed interactions with regolith surfaces have been studied mainly through laboratory experiments of impacts into granular matter in Earth gravity (U2003, KD2013) and in environments that can simulate low-gravity interactions for a limited time (Brisset et al 2018;Murdoch et al 2021). As we have demonstrated, numerical simulations of granular material are an invaluable tool for exploring these low-energy impact regimes, as we are able to simulate the lowgravity environment of small asteroids easily and recreate the detailed MNRAS 507, 5087-5105 (2021) design characteristics of spacecraft devices or landers (Maurel et al 2018;Thuillet et al 2018;C ¸elik et al 2019.…”
Section: Low-energy Events On Asteroidsmentioning
confidence: 99%
“…To further validate the collision behavior of impact tests, quantities including the peak acceleration of the projectile, penetration depth, and collision time were evaluated and compared against experimental and numerical results [71,72]. Note that the simulation herein used monodisperse particles, whereas polydisperse ones were employed in [72].…”
Section: Low-velocity Cratering Testmentioning
confidence: 99%